Trade facilitation measures that are necessary, but not sufficient, to improve trade across borders performance - Wong Chan, Susana (Centro de Investigación y Capacitación en Administración Pública, 2024)
In 2013, the negotiations for the Trade Facilitation Agreement (TFA) of the World Trade Organization were concluded. Attempts have been made to quantify the impact of TFA implementation on global trade cost and time reduction. For example, a study has determined that the implementation of TFA measures can reduce global trade costs between 10% and 18%, depending on the country. However, more guidance is needed to understand which specific TFA measures are necessary to reduce the time and cost of cross-border trade. Therefore, this study uses a novel quantitative method called “Necessary Condition Analysis” that allows identifying the TFA measures that are necessary to reduce cross-border trade costs and time, but that may not be sufficient to achieve said objective since they may depend on additional factors. But if the necessary conditions are not present, it would be impossible to achieve the desired outcome. This study found that 84 TFA measures, which represents 54.2% of the total analyzed measures, can be considered as necessary, but not sufficient, to achieve high Trading across Borders performance. Ten out of the 84 TFA measures are considered to have a medium or large effect. These ten measures are: independent or higher-level administrative and/or judicial appeal procedures available for customs decisions; establishment of a national customs website; public consultations between traders and other interested parties and government; possibility to provide online feedback to Customs; information on import and export procedures; average clearance time; time to prepare documents for import; time to prepare documents for export; use of pre-shipment inspections required on Customs matters; targeted stakeholders; international Standards compliance; and release of goods separated from the final determination and payment of Customs duties.